The MOPEAD project: Advancing patient engagement for the detection of "hidden" undiagnosed cases of Alzheimer's disease in the community. Issue 6 (7th May 2019) - Rodríguez‐Gómez, Octavio; Rodrigo, Adrián; Iradier, Fátima; Santos‐Santos, Miguel A.; Hundemer, Hans; Ciudin, Andreea; Sannemann, Lena; Zwan, Marissa; Glaysher, Bridget; Wimo, Anders; Bonn, Jaka; Johansson, Gunilla; et al.
Abstract: In most, if not all health systems, dementia is underdiagnosed, and when diagnosis occurs, it is typically at a relatively late stage in the disease process despite mounting evidence showing that a timely diagnosis would result in numerous benefits for patients, families, and society. Moving toward earlier diagnoses in Alzheimer's disease (AD) requires a conscientious and collective effort to implement a global strategy addressing the multiple causes hindering patient engagement at different levels of society. This article describes the design of the Models of Patient Engagement for Alzheimer's Disease project, an ongoing EU‐funded public‐private multinational initiative that will compare four innovative patient engagement strategies across five European countries regarding their ability to identify individuals with prodromal AD and mild AD dementia, which are "hidden" in their communities and traditionally not found in the typical memory clinic setting. The strategies include an online AD citizen science platform, an open house initiative at the memory clinics, and patient engagement at primary care and diabetologist clinics.